O patrimônio material local digitalizado : um circuito histórico a serviço do ensino de história - Costa, Camillo Gustavo Xavier (2022)
This dissertation aims to offer different alternatives to dynamize History Teaching, as well as work with Local History and Material Cultural Heritage, through the use of Digital Information and Communication Technologies, such as the QR Code and Web Site. With this work, it was intended to develop in Sergipe students historical awareness and empathy, zeal for the Heritage of the Historic Center of Aracaju, knowledge and appreciation for Local History, giving it meaning, as well as contributing to overcoming traditionalism in teaching. We identified in our research, that in Elementary School Final Years, there is a lack of didactic material that deals with Local History, material that is based on the skills and abilities covered in the Sergipe Curriculum. Seeking to fill this gap, we developed a teaching aid to be used by teachers and students from Sergipe in the 8th and 9th grades of private and public schools. We understand the monument as a document, we see ourselves as a link between the present and the past. With this understanding, we created a Circuit of visitation to the material heritage, which we called Historic Circuit, consisting of two historical-heritage sequences and involving eight monuments. It is based on National-Local History and is based on the experimentation of heritage, whether through digital and (or) physical means, considering its opposition and taking it in an investigative way. Authors such as Le Goff (1990 and 2013), Jörn Rüsen (2010), Cerri (2011), Lee (2003, 2006 and 2016) and Pelegrini (2009) form our theoretical field.